Study on multi-scale damage and failure mechanism of steel fiber reinforced concrete: Experimental and numerical analysis. (February 2023) - Lu, Fucong; Xu, Jiubao; Li, Weijia; Hou, Yuhang; Qin, Fangping; Pan, Mingzhang
Abstract: The damage and failure behavior of steel fiber reinforced concrete (SFRC) is extremely complex. The reinforcement mechanism of steel fiber to concrete and the meso-failure mechanism of SFRC have not been thoroughly researched. This paper studied the mechanical behavior of SFRC from two perspectives: macro lab experiment and meso-numerical simulation. Firstly, macro-tests were conducted to examine the effects of the volume content and the length-to-diameter ratio of copper coated microfilament steel fiber on the mechanical properties of SFRC. The result shows that when the volume content of steel fiber is 2% and the length-to-diameter ratio of steel fiber is 60, the cubic compressive strength, splitting tensile strength and flexural tensile strength of SFRC are improved the most, which are 33.1%, 121%, and 35% higher than that of plain concrete respectively. Secondly, three empirical formulas of the compressive strength, splitting strength, and flexural strength of SFRC considering the influence of steel fiber parameters were proposed and the characteristics and phenomena of concrete and SFRC in each stage of compression failure were studied. Thirdly, this work proposed a simple and efficient three-dimensional method for modeling SFRC. The simulation accurately predicted the failure mode and mechanical property response of SFRC. In addition, the effects of steel fiber volume content, length-to-diameter ratio, and friction coefficient of contact surface on the mechanical behavior of SFRC composites were discussed by the model.